The impact of genetic polymorphisms of IL28B gene on the efficacy of antiviral therapy of the chronic hepatitis C by using the standard Interferon-α - A. V. Lapshin; M. V. Mayevskaya; V. T. Ivashkin; P. O. Bogomolov; I. G. Nikitin; O. O. Znoyko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the Study. To analyze the predictive value of the genetic polymorphisms in rs8099917 and rs12979860 loci of the IL28В gene for the assessment of the efficacy prognosis of the combined antiviral therapy on the basis of the standard Interferon of the patients with Chronic Hepatitis C (CHC).Materials and Methods. The study of IL28B genetic polymorphisms was conducted in 66 patients with HCV who did not receive the treatment earlier. The 24- week or 48-week antiviral therapy by standard Interferon-α2b and Ribavirin was prescribed to all patients, taking into consideration the genotype of the HCV-infection. The analysis of the efficacy of the treatment was conducted on the basis of the assessment of the normalization of the biochemical cytolysis markers during and after the treatment as well as the availability of the rapid, early and stable virology response.Results. Among the patients with 1-st HCV genotype, the favorable genotype IL28В of alleles rs12979860 and rs8099917 (СС/ТТ) were associated with consider- ably higher frequency of the stable virology response than different versions of unfavorable genotype IL28В. Among the patients who did not have 1-st genotype the polymorphisms of IL28B gene did not affect the efficacy of antiviral therapy .Conclusion. The studies of genetic polymorphisms of the regions of human genome demonstrates that the positive predictive value of IL28B polymorphisms among the patients with 1-st HCV genotype is higher than among the patients with 2nd and 3d genotypes. This kind of approach enables to take into account the pharmaco-economic aspect of the treatment of chronic HCV-infection.